Increased Osmolarity in Biofilm Triggers RcsB-Dependent Lipid A Palmitoylation in Escherichia coli - Magdalena Szczesny (American Society for Microbiology, 2018)
ABSTRACT Biofilms are often described as protective shelters that preserve bacteria from hostile surroundings. However, biofilm bacteria are also exposed to various stresses and need to adjust to the heterogeneous physicochemical conditions prevailing within biofilms. In Gram-negative bacteria, such adaptations can result in modifications of the lipopolysaccharide, a major component of the outer membrane characterized by a highly dynamic structure responding to environmental changes. We previously showed that Gram-negative biofilm bacteria undergo an increase in lipid A palmitoylation mediated by the PagP enzyme, contributing to increased resistance to host defenses. Here we describe a regulatory pathway leading to transcriptional induction of pagP in response to specific conditions created in the biofilm environment. We show that pagP expression is induced via the Rcs envelope stress system independently of the Rcs phosphorelay cascade and that it requires the GadE auxiliary regulator. Moreover, we identify an increase in osmolarity (i.e., ionic stress) as a signal able to induce pagP expression in an RcsB-dependent manner. Consistently, we show that the biofilm is a hyperosmolar environment and that RcsB-dependent pagP induction can be dampened in the presence of an osmoprotectant. These results provide new insights into the adaptive mechanisms of bacterial differentiation in biofilm. IMPORTANCE The development of the dense bacterial communities called biofilms creates a highly heterogeneous environment in which bacteria are subjected to a variety of physicochemical stresses. We investigated the mechanisms of a widespread and biofilm-associated chemical modification of the lipopolysaccharide (LPS), a major component of all Gram-negative bacterial outer membranes. This modification corresponds to the incorporation, mediated by the enzyme PagP, of a palmitate chain into lipid A (palmitoylation) that reduces bacterial recognition by host immune responses. Using biochemical and genetic approaches, we demonstrate that a significant part of biofilm-associated lipid A palmitoylation is triggered upon induction of pagP transcription by the hyperosmolar biofilm environment. pagP induction is regulated by RcsB, the response regulator of the Rcs stress response pathway, and is not observed under planktonic conditions. Our report provides new insights into how physiological adaptations to local biofilm microenvironments can contribute to decreases in susceptibility to antimicrobial agents and host immune defenses.